Voluntary exercise in mice triggers an anti-osteogenic and pro-tenogenic response in the ankle joint without affecting long bones - Anne Briolay; François Duboeuf; Séverine Delplace; Leyre Brizuela; Olivier Peyruchaud; David Magne; Carole Bougault (Bone Reports, 2024)
Biomechanical stimulation is proposed to occupy a central place in joint homeostasis, but the precise contribution of exercise remains elusive. We aimed to characterize in vivo the impact of mechanical stimulation on the cell-controlled regulation of ossification within the ankles of healthy mice undergoing mild physical activity. DBA/1 male mice were subjected to voluntary running exercise for two weeks, and compared to mice housed in standard conditions (n = 20 per group). Free access to activity wheels resulted in a running exercise of 5.5 ± 0.8 km/day at 14.5 ± 0.5 m/min. Serum levels of alkaline phosphatase, IL-6, IL-8/Kc, IL-17a, and TNF-α were measured. No change in systemic inflammation was detected. The bone architecture of the femur and the calcaneus was unchanged, as revealed by μCT and histology of the enthesis of the Achilles tendon. mRNAs were extracted from femurs, tibias, and ankle joints before RT-qPCR analysis. The expression of the mechanosensitive genes Sclerostin (Sost) and Periostin (Postn) was not impacted by the exercise in long bones. Oppositely, Sost and Postn levels were modulated by exercise in joints, and osteogenic markers (Col10a1, Runx2, Osx, and Dmp1) were downregulated in the exercise group. In addition, the tenogenic markers Scx, Mkx, and Tnmd were upregulated by exercise. Thus, voluntary exercise affected the phenotype of joint cells without impacting long bones. As gene expression of Bmp2, Bmp4, and Id1 was also reduced in these cells, an off-regulation of BMP signaling could be partly responsible for their mechanosensitive response. Running exercise seemed to preserve the tendon from its progressive ossification, as seen in numerous enthesopathies. This study paves the way to future experiments for investigating the effects of mechanical stimulation in various mouse models.